Species-specific sensitivity to PAHs reveals widespread biodiversity impact from the 2021 oil spill in the Eastern Mediterranean - Omri Lapidot; Natalie Perlin; Eli Biton; Pavel Khain; Yoav Levi; Pinhas Alpert; Debra Ramon; Nir Stern; Gil Rilov; Tamar Guy-Haim; Yoav Lehahn; Claire B. Paris; et al. (Marine Pollution Bulletin, 2026)

Assessment of potential toxic elements accumulation and consumption risk in fishery resources of the southeast Mediterranean Sea - Guy Sisma-Ventura; Yael Segal; Aviv Shachnai; Maya Mar Mori; Maria Abu Hadra; Eli Biton; Or.M. Bialik; Nir Stern; Barak Herut (Marine Pollution Bulletin, 2026)

Coastal-to-offshore submesoscale horizontal stirring enhances wintertime phytoplankton blooms in the ultra-oligotrophic Eastern Mediterranean Sea - Yotam Fadida; Vicky Verma; Roy Barkan; Eli Biton; Aviv Solodoch; Yoav Lehahn (Ocean Science, 2026)
The large seasonal increases in marine photosynthetic organisms – i.e., phytoplankton blooms – are a ubiquitous oceanic phenomenon that contributes to the removal of carbon dioxide from the atmosphere and supports the growth of larger marine organisms. The underlying mechanisms controlling the intensity and timing of these blooms have been proposed to be dominated by vertical transport and mixing processes that are enhanced at fine-scale frontal and filamental circulations, commonly known as submesoscale currents. Here we show that the winter blooms characteristic of the ultra-oligotrophic waters of the Eastern Mediterranean Sea, which manifest as a seasonal increase in satellite-derived levels of surface chlorophyll, are intensified by enhanced horizontal stirring induced by the submesoscale currents. Using ocean color remote sensing data and high-resolution numerical simulations, we demonstrate that the intensification of submesoscale currents in winter efficiently connect the coastal waters and the ultra-oligotrophic open-sea waters, thereby enriching the latter with chlorophyll-rich waters. A climatological chlorophyll time series comparison between two different regions equidistant to the Nile River Delta indicates that this submesoscale horizontal stirring mechanism accounts for the ∼ 24.8 % larger wintertime increase in surface chlorophyll observed downstream of the Nile Delta. These results shed new light on the processes governing phytoplankton bloom intensity and emphasize the important role of submesoscale horizontal stirring in modulating the marine ecosystem.

Long-term (1979–2024) trends and remobilization process of mercury pollution, the case study of Haifa Bay, Southeast Mediterranean Sea - Guy Sisma-Ventura; Yael Segal; Yaron Gertner; Maya Mar Mori; Maria Abu Hadra; Eli Biton; Aviv Shachnai; Barak Herut (Journal of Hazardous Materials, 2025)

Observations of turbidity currents in a small, slope-confined submarine canyon in the Eastern Mediterranean Sea - Roy Jaijel; Eli Biton; Yishai Weinstein; Tal Ozer; Timor Katz (Earth and Planetary Science Letters, 2023)

Post-eastern Mediterranean Transient Oxygen Decline in the Deep Waters of the Southeast Mediterranean Sea Supports Weakening of Ventilation Rates - Guy Sisma-Ventura; Nurit Kress; Jacob Silverman; Yaron Gertner; Tal Ozer; Eli Biton; Ayah Lazar; Isaac Gertman; Eyal Rahav; Barak Herut (Frontiers in Marine Science, 2021)
Long-term trends in oxygen, salinity, and nutrients were followed in the Southeastern Mediterranean (SEMS) deep waters from 2002 to 2020. Results show a net decrease in oxygen since 2008 of −0.5 ± 0.1 μmol kg −1 yr −1 in the bathypelagic depths (1,200–2,000 m). Multiannual variability in oxygen levels superimposed this trend, and is likely associated with variations in thermohaline fluxes. The 2020 mean oxygen concentration of 179.5 ± 2.3 μmol kg −1 is comparable to the pre-Eastern Mediterranean Transient (EMT) mean value. The post-EMT signature is clearly demonstrated in both oxygen and salinity over the period of 2002–2013, but since 2014 it diminished, mainly due to mixing of the Aegean deep water (AegDW) mass with the overlying old Adriatic water mass. This trend reflects a switch back to the pre-EMT regime, characterized by thermohaline homogeneity of the deep water column in the SEMS. The long-term decline of deep water oxygen levels is also accompanied by a corresponding increase in dissolved inorganic nutrients, supporting aging of the deep water masses. Our results suggest that ventilation of the SEMS deep water is currently occurring at a lower, pre-EMT rate, probably as a result of moderated deep water formation in recent time.